Moderate UVB exposure ameliorate chronic stress-induced anxiety and social impairment by activating mPFC to basal lateral amygdala pathway - Dake Song; Jingyu Qi; Yingying Zhang; Ruixia Liu; Min Wang; Xinshang Wang; Yumei Wu; Xubo Li; Kun Zhang; Shuibing Liu (Brain Research Bulletin)
Ultraviolet radiation B (UVB), the most biologically active ultraviolet ray in sunlight, exert broad effects on physiological and behavioral functions, including circadian rhythm, mood, and cognition. However, its underlying mechanisms are still unknown. In this study, in order to verify effects of UVB on anxiety and social behaviors, C57BL/6 mice receiving 2 h UVB exposure after chronic restraint stress were used. UVB exposure improved anxiety-like behaviors and social activities in normal and restraint stressed mice. Meanwhile, UVB exposure increased the neural excitability in mPFC according to cFos staining and electrophysiology results. And benefits of UVB exposure could be blocked by chemogenetical inhibition of mPFC or inhibiting mPFC to basal lateral amygdala (BLA) pathway. In conclusion, we identify UVB exposure ameliorate chronic stress-induced anxiety and social impairment by activating mPFC to BLA pathway. The series of research may lead to the development of UVB as a novel therapeutic approach for treating anxiety and social avoidance in the future.